PENGARUH LIKUIDITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN DAN MENAJEMEN ASET TERHADAP KINERJA KEUANGAN PERUSAHAAN - Aurellia Regina Rhadif; Luh Putu Puji Trisnawati (JURNAL LENTERA AKUNTANSI, 2024)
This study aims to examine the influence of liquidity, capital structure, company size, and asset management on company financial performance. The population of this research consists of all healthcare and pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The research data was collected using secondary data through a purposive sampling technique. The sample size includes 12 companies, resulting in a total of 60 observations. The study employs analysis techniques such as classical assumption tests, including normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Hypothesis testing is conducted using multiple regression analysis with SPSS version 26. The research results indicate that liquidity and capital structure do not affect company financial performance, as their significance values are greater than 0.05. Meanwhile, the variables of company size and asset management have an impact on company financial performance, with significance values of 0.040 and 0.005, respectively.